A case for characterizing declarative memory commission errors in healthy aging - Popoviciu, Ariana; Richmond, Lauren L. (Frontiers in Cognition, 2025)
Cognitive psychologists typically characterize declarative memory performance in terms of omission errors, or information that is not reported at test. At the same time, there tends to be much less attention paid to characterizing errors of commission, such as reporting non-studied items at test. Importantly, older adults are known to make both types of errors in declarative memory tasks more often than young adults. This review aims to encourage a more thorough characterization of age-related commission errors in declarative memory research by synthesizing findings from disparate literatures that have taken an interest in characterizing this type of error. Specifically, findings relating to commission errors from the false memory, associative memory, and hyper-binding literatures are reviewed to demonstrate the utility of characterizing older adults' declarative memory performance by accounting for commission errors. Together, existing cognitive data provide a compelling rationale for memory researchers, and particularly those interested in age-related changes in memory, to characterize performance by accounting for commission errors in addition to the more commonly considered omission errors.